Management of Biliary Complications in Liver Transplant Recipients with Duct-To-Duct Anastomosis: A Single-Center Experience - Muhammed Fatih Karakaya,; Erdem Er,; Onur Kırımker,; Mesut Gümüşsoy,; Emin Bodakçi,; Mubin Özercan,; Beyza Doğanay Erdoğan,; Hale Gökcan,; Meltem Koloğlu,; Kaan Karayalçın,; Cihan Yurdaydın,; Acar Tüzüner,; et al. (Turkish Journal of Gastroenterology, 2023)
Background: The aims of this study were to investigate biliary complications in liver transplant recipients with choledochocholedocho stomy anastomosis, to identify the risk factors for the development of such complications, and to evaluate the success of endoscopic approaches in liver transplant recipients.Methods: Between January 2013 and May 2021, a total of 238 patients with liver diseases underwent liver transplantation: 174 recipients undergoing choledochocholedochostomy anastomosis were included in the analysis.Results: Their median age was 54.0 years. The median posttransplant follow-up period was 29 months. Hepatitis B virus infection (33%) was the most common indication for liver transplantation. Most patients (87%) received living donor liver transplantation. The overall prevalence of posttransplant biliary complications was 31%. Anastomotic biliary strictures were the most common biliary complications (72%), followed by biliary leakage (13%). The median time between endoscopic retrograde cholangiography and liver transplantation was 4 months, with a mean of 3 ± 1.6 sessions. Endoscopic retrograde cholangiography-guided drainage and balloon dilation with or without stent placement was the most common treatment modalities for recipients with biliary strictures. The overall success rate of endoscopic treatment modalities was 83.3%, with 65% of the recipients exhibiting complete biochemical and endoscopic responses. The response did not differ significantly between living donor liver transplantation and cadaveric donor liver transplant recipients (P > .05). Three recipients required revision surgery for biliary complication repair. Six patients died due to biliary sepsis.Conclusion: Biliary stricture and leakages were the most common biliary complications after liver transplantation. Endoscopic treatment was successful in most recipients.Cite this article as: Karakaya MF, Er E, Kırımker O, et al. Management of biliary complications in liver transplant recipients with duct-to-duct anastomosis: A single-center experience. Turk J Gastroenterol. 2023;34(2):177-181.